The Influence of Organizational Culture, Leadership Style and Compensation on Employee Performance - Sumantri, Bambang; Pujiati, Herni (Dinasti International Journal of Management Science, 2025)
This study aims to analyze the influence of organizational culture, leadership style, and compensation on employee performance. A strong organizational culture can create a conducive work environment, increase motivation, and strengthen employee commitment to company goals. An effective leadership style also plays an important role in motivating employees to achieve their best performance, by providing clear direction and creating a mutually supportive relationship between leaders and team members. Fair and competitive compensation not only serves as a reward for achievement but also as a tool to retain the best talent in the company. This study uses a qualitative approach with a library research method using journal literature reviews, where data is collected through journal reviews in various industrial sectors. The results of the analysis show that organizational culture, leadership style, and compensation have a significant influence on employee performance simultaneously. Individually, organizational culture and compensation are proven to have a stronger relationship to performance improvement, while leadership style also has a significant impact at a lower level. This research provides insight for companies in designing managerial strategies to improve performance through effective management of organizational culture, leadership style, and compensation systems.